(untitled) (MAUSAM, 2014)
The aim of the present study is to investigate the temperature and snowfall trends in the cryosphere region of north-west Himalaya during winter season. 37 observation stations of North-West Himalaya have been considered for the study and these stations receive snowfall during winter season. The snow meteorological data period of the parameters maximum temperature, minimum temperature and snowfall varied from one observation station to other observation station between 1970 to 2011. Monthly and seasonal trends of these parameters during winter have been studied. Linear regression analysis was used for trend analysis. Parametric t-test was used to test the significance of the regression coefficient. Altitude effect in the trends of the meteorological parameters has been noticed. It was observed that more than 75% of the observation stations in the altitude range < 4000 m a.s.l. showed increasing trend in maximum temperature and minimum temperature during winter season, out of which around 25% trends were statistically significant. Most of the observation stations in the altitude range > 4000 m showed decreasing trend of maximum and minimum temperature. Decreasing snowfall trend was observed at most of the stations in the altitude range < 4000 m out of which around 20% trends were statistically significant. Significant decrease in snowfall was observed for the months March and April below 4000 m altitude.